-9a-10(a-1)=10(6a+1)

Simple and best practice solution for -9a-10(a-1)=10(6a+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9a-10(a-1)=10(6a+1) equation:



-9a-10(a-1)=10(6a+1)
We move all terms to the left:
-9a-10(a-1)-(10(6a+1))=0
We multiply parentheses
-9a-10a-(10(6a+1))+10=0
We calculate terms in parentheses: -(10(6a+1)), so:
10(6a+1)
We multiply parentheses
60a+10
Back to the equation:
-(60a+10)
We add all the numbers together, and all the variables
-19a-(60a+10)+10=0
We get rid of parentheses
-19a-60a-10+10=0
We add all the numbers together, and all the variables
-79a=0
a=0/-79
a=0

See similar equations:

| (-x-9)×1=(9x-3)(-1) | | x+0.5=8.5 | | 18x+-36+26=-10 | | 5s=8+4s | | 1.45x=57 | | −3(x+3)=−3x–9 | | 2(3x–1)=–20 | | 18.2+y=–16.8 | | 7=8+a/2 | | 0.05x+3-0.02=42 | | n+3.1=5 | | −11x=−77 | | 5.1g+4=3.1+10 | | -9p+17=62 | | 180=3x+4=2x+3x | | 3x=223 | | r-1823=23102 | | 11n+14=95−16n | | -1÷2(12v-20)+4=-12-8v | | 7x-9*x=90 | | 3+15y=30 | | -5(5-4)=10(2+9n)+6n | | 3x+4=2x+3x | | 11=20+r | | 13(9x−6)=22−5x | | 3x+4+11=30 | | 2x-9+x+5=157 | | 12a=8-12a+8 | | 4=p−559 | | 17+2q=13 | | 7(8-2x)=-9(x+1)-55 | | 8n+5n=42 |

Equations solver categories